Semi-ideal Bidding via a fuzzy TOPSIS project evaluation framework in risky environments - Ravanshadnia, Mehdi; Rajaie, Hossein (Journal of Civil Engineering and Management, 2014)
Blind involvement in aimless bids may result the loss of bidding bond expenditures, purchased bidding documents, the cost of human resources engaged in mark-up estimation, and detailed project investigation costs such as site visits. In this research, a risk based fuzzy TOPSIS framework is set up to evaluate and prioritize bidding opportunities. This may help contractors to assign their limited resources to near optimal selected projects. The risks inherent in the nature of every tender, makes systematic risk analysis a prerequisite for any construction company. Proposed framework considers key determining risk factors such as corporate considerations, tender environment, contractual issues, and project specific risks. The methodology implementation has been facilitated by developing a graphical user interface that accepts linguistic terms expressed by main decision groups. A case study demonstrates the applicability of the model.